High thermoelectric properties realized in earth abundant Bi2S3 bulk materials via Se and Cl co-doping in solution synthesis process. (20th February 2022) - Guo, Jun; Zhu, Yu-Ke; Chen, Lin; Wang, Zi-Yuan; Ge, Zhen-Hua; Feng, Jing
Highlights: Se and Cl co-doped nanostructured Bi2 S3 powders were successfully synthesized via hydrothermal. A high σ value of 483 S cm −1 is obtained at 300 K for the Bi2 S2.4 Se0.4 Cl0.20 sample. A high PFave. of 411 μW m −1 K −2 is achieved for the Bi2 S2.4 Se0.4 Cl0.20 . The highest ZT value of 0.66 is achieved at 673 K for the Bi2 S2.4 Se0.4 Cl0.20 sample. Abstract: Bi2 S3 -based alloys are considered promising thermoelectric materials due to their large Seebeck coefficient and low lattice thermal conductivity. However, low electrical conductivity usually leads to poor electrical transport properties, which seriously restricts their further application in thermoelectric refrigeration and/or power generation. In this work, Bi2 S3 with high electrical transport properties is synthesized hydrothermally via Se and Cl co-doping. The maximum electrical conductivity value of 483 S cm −1 was obtained for the Bi2 S2.4 Se0.4 Cl0.20 sample at room temperature. The significant improvement of electrical conductivity gives rise to a high average power factor of 411 μW m −1 K −2 during the measuring temperature range and a peak value of 456 μW m −1 K −2 at 673 K. Benefiting from the largely improved electrical transport properties, a superior ZT value of approximately 0.66 and ZTave . of 0.36 were obtained for Bi2 S2.4 Se0.4 Cl0.20, and the theoretically calculated conversion efficiency reached 5.7%. The results indicate that Bi2 S3 is a promising candidate for thermoelectric applications at medium temperatures. Graphical abstract: Image, graphical abstract A high ZT value in Bi2S3 system of ∼0.66 was achieved at 673 K for Bi2S3 with Se and Cl co-doped through a facile hydrothermal followed by spark plasma sintering.